Effect of Erbium:YAG Laser Recycling on Mechanical Characteristics of Retrieved Orthodontic Mini-screws: Effect of erbium:YAG laser recycling on retrieved orthodontic mini-screws - Yassaei, Soghra; Aghili, Hossein; Behrouzirad, Atie (Journal of Lasers in Medical Sciences, 2023)
Introduction: This study aimed to evaluate the influence of two recycling methods on the mechanical and surface characteristics of orthodontic mini-screws. Methods: Thirty-six retrieved mini-screws were randomly classified into two equal groups. In the first group (laser recycled group (LG)), the Er:YAG laser (2940 nm, 5.5 W, 275 mJ, perpendicular to the mini-screws at a distance of 7-10 mm, 25 s) was used to recycle mini-screws. In the second group (phosphoric acid and sodium hypochlorite recycled group (ASG)), the mini-screws were kept in 37% phosphoric acid gel (10 minutes) and then placed in 5.25% sodium hypochlorite for 30 minutes. Eighteen new mini-screws were selected as the control group (CG). Maximum insertion torque (MIT), maximum removal torque (MRT), and fracture torque (FT) of all mini-screws were measured. A sample from each group was examined for the surface changes of the mini-screw and tissue remnants under a scanning electron microscope (SEM). Results: The mean MIT was significantly higher in both LG and ASG groups than the CG (P<0.001 and P=0.002, respectively). However, no significant difference was shown between the LG and ASG groups. The mean values of MRT and FT showed no significant difference between the groups. The amount of tissue remnants in the ASG group was significantly higher than that in the LG group. The evidence of porosity and corrosion was observed on the ASG mini-screw surface, and there was an increase in roughness on the LG mini-screw surface. Conclusion: The Er: YAG laser recycling of mini-screws is a proper method causing minimum damage to the screw surface.